Fabrication of Ni-MOF74 derived Ni-carbon material for the highly efficient H2 gas adsorption at mild operating condition. (30th September 2022) - Seema, Humaira; Kemp, Christian; Subhan, Sidra; Yaseen, Muhammad
Abstract: This study fabricates nickel nanoparticle-carbon hybrid (Ni-MOF74) composite via solvothermal technique, and carbonized at different temperature under inert atmosphere, which was then used for the hydrogen storage. Morphology, crystallinity, electronic distribution and other surface properties of the synthesized material were extensively checked via different analytical techniques. Results showed that the Ni-MOF74 sample carbonized at 500 °C displays an improved hydrogen storage capacity of∼400% compared to the parent Ni-MOF74 material (0.088 vs 0.002 wt %), at 298 K and 1 atm. We believe that these Ni-carbon hybrid materials hold promising results for hydrogen storage as they show potential for storage at room temperature, and it is believed to be cost effective compared to traditionally used hydrogen spillover catalysts. Graphical abstract: Image 1 Highlights: The Ni NPs based carbon material was produced via carbonization of Ni-MOF74 under an inert atmosphere. H2 storage was achieved at room temperature using a Ni NPs carbon material. H2 storage over Ni NPs carbon material occurred through the hydrogen spillover mechanism. Ni NPs carbon material showed high H2 storage capacity than the pristine Ni-MOF74.